O7.4. ASSOCIATIONS BETWEEN DOPAMINE SYNTHESIS CAPACITY, GLUTAMATE AND GABA LEVELS IN ANTIPSYCHOTIC-NAïVE PATIENTS WITH FIRST EPISODE PSYCHOSIS. (9th April 2019) - Sigvard, Anne; Bojesen, Kirsten; Tangmose, Karen; Jessen, Kasper; Nielsen, Mette Ødegaard; Fuglø, Dan; Jensen, Lars Thorbjørn; Rostrup, Egill; Glenthoj, Birte
Abstract: Background: Disturbances in the interacting dopaminergic, glutamatergic and GABAergic systems in the cortico-striato-thalamo-cortical circuits in the brain have been implicated in the pathophysiology of psychosis. Preclinical literature suggests that these disturbances are linked to each other, whereas recent clinical data have pointed to separate subgroups of patients characterized by either glutamatergic or dopaminergic abnormalities. In the present study we explore the associations between dopamine synthesis capacity and glutamate and GABA levels in antipsychotic-naïve first-episode psychosis (FEP) patients. Methods: The study is ongoing. We have now processed magnetic resonance spectroscopy (MRS) and positron emission tomography (18F-FDOPA-PET) data on 22 patients (32% males, mean age 22 (±4.3)) and 18 controls (50% males, mean age 22 (±2.7)). All patients are strictly antipsychotic-naïve and have no substance abuse. The diagnosis is validated with a diagnostic interview. The patients fulfill the criteria for schizophrenia (n:15), non-organic psychosis (n:5), schizoaffective disorder (n:1) or paranoid psychosis (n:1). They are moderately ill with a mean total score of 78 (±9.6) on the Positive and Negative Syndrome Scale. Glutamate and GABA-levels in the anterior cingulate cortex (ACC) are obtained with MRS. Dopamine synthesis capacity in striatum is measured with 18F-FDOPA-PET. The mean dopamine synthesis capacity is extracted from the whole striatum. Additionally, striatal subregions are defined anatomically (nucleus accumbens, nucleus caudatus and putamen, left and right) and subregional dopamine synthesis capacities are obtained. The association between dopamine synthesis capacity and levels of glutamate and GABA in patients and controls is assessed with linear regression with dopamine synthesis capacity as dependent variable and group and GABA or glutamate as independent variables. Analyses are performed with and without adjustment for age and sex. Results: High dopamine synthesis capacity in the total striatum is associated with low ACC glutamate levels in patients (p=.03), but not in controls. This association remains significant after adjusting for age and sex (p=.02). In all subjects, dopamine synthesis capacity in the left caudate is positively correlated with ACC GABA (p<.05), although not after adjusting for age and sex (p=.08). In controls only, there is a positive association between dopamine synthesis capacity in right caudate and putamen and ACC GABA levels (p<.01 and p=.01 respectively). Discussion: The present data shows an inverse relationship between glutamate levels in the ACC in antipsychotic-naïve FEP patients and striatal dopamine synthesis capacity, hereby contradicting the notion of two distinct subgroups of patients characterized by either abnormal striatal dopamine or cortical glutamate activity. In healthy controls we find a strong positive association between ACC GABA levels and dopamine synthesis capacity, which is only present unilaterally and to a much smaller degree in patients. Taken together, the data supports that disturbances in the interacting dopaminergic, glutamatergic and GABAergic systems in the macro circuits in the brain are implicated in the pathophysiology of psychosis. Since the patients had never received any antipsychotic medication (lifetime), these disturbances are not related to antipsychotic treatment. The data represents work in progress. Inclusion and data processing are ongoing hence more detailed data analysis on a larger sample size and analyses including psychopathology will be presented at the conference.